2021
DOI: 10.3389/ijph.2021.643486
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward COVID-19 Vaccination Among Young Adults in Zurich, Switzerland, September 2020

Abstract: Objectives: Young adults are essential to the effective mitigation of the novel coronavirus (SARS-CoV-2/COVID-19) given their tendency toward greater frequency of social interactions. Little is known about vaccine willingness during pandemics in European populations. This study examined young people’s attitudes toward COVID-19 vaccines in Fall 2020.Methods: Data came from an ongoing longitudinal study’s online COVID-19-focused supplement among young adults aged 22 in Zurich, Switzerland (N = 499) in September … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
5
5
0
Order By: Relevance
“…In both groups, women reported higher levels of anxiety toward COVID-19, but lower levels of confidence in vaccine safety, and less willingness to get vaccinated than men. These findings are consistent with several studies that found a negative association between women and the intention to vaccine against COVID-19 in the general population of different countries (including China, France, Switzerland, Australia, Pakistan, the United States, and a number of countries in the Middle East, among others) [6] , [7] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [32] , [33] , [34] . However, when we evaluated the effect of all acceptance factors on willingness to get vaccinated, we found a significant association between gender and vaccination willingness only among people with diabetes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In both groups, women reported higher levels of anxiety toward COVID-19, but lower levels of confidence in vaccine safety, and less willingness to get vaccinated than men. These findings are consistent with several studies that found a negative association between women and the intention to vaccine against COVID-19 in the general population of different countries (including China, France, Switzerland, Australia, Pakistan, the United States, and a number of countries in the Middle East, among others) [6] , [7] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [32] , [33] , [34] . However, when we evaluated the effect of all acceptance factors on willingness to get vaccinated, we found a significant association between gender and vaccination willingness only among people with diabetes.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies found that concerns about vaccine safety, adverse effects, and effectiveness negatively impacted its acceptance [e.g., 6, 9]. Several studies reported that women were more concerned about vaccination than men [6] , [7] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] . Further, as Joshi et al [6] and El-Elimat et al [18] have shown, having been vaccinated against the seasonal influenza was identified as a positive factor in vaccine acceptance.…”
Section: Introductionmentioning
confidence: 99%
“…Forwarding the effective messages to the public concerning this vaccine is crucial to promote the acceptance of this vaccine [ 120 ]. Campaigns to disseminate information are also vital to promote participation in the immunization of COVID-19 pandemic [ 121 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that for any nation, young adults proved indispensable for mitigation of the SARS-Cov-2. Higher participation from them in immunization programs is required and they need to be engaged in the advocacy and mobilization of vaccination initiatives (Leos-Toro et al, 2021). Quality of information diffused through all the sources proved critical during any health crisis.…”
Section: Analysis and Discussionmentioning
confidence: 99%